2003
DOI: 10.1148/radiol.2273020535
|View full text |Cite
|
Sign up to set email alerts
|

Myelomeningocele: Prenatal Evaluation—Comparison between Transabdominal US and MR Imaging

Abstract: Findings at prenatal MR imaging and prenatal US are equally accurate for the assignment of a lesion level in a fetus with myelomeningocele. Given that findings with both modalities will lead to misdiagnosis of the spinal level by two or more segments in at least 20% of cases, care should be exercised when neurologic outcome is predicted on the basis of these studies alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 18 publications
4
44
2
2
Order By: Relevance
“…Patient stratification, however, remains challenging and can present as significant ethical dilemmas, especially in light of the fact that prenatal repair and termination of pregnancy are among the options to be considered [1]. At this time, prenatal staging of NTDs is done primarily by imaging, which can provide both anatomical and functional information, yet it has been of limited prognostic value [1,2,3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Patient stratification, however, remains challenging and can present as significant ethical dilemmas, especially in light of the fact that prenatal repair and termination of pregnancy are among the options to be considered [1]. At this time, prenatal staging of NTDs is done primarily by imaging, which can provide both anatomical and functional information, yet it has been of limited prognostic value [1,2,3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the intrauterine MMC surgical repair substantially reduced the incidence of shunt-dependent hydrocephalus with most of this benefit for the MMC lesions located below L3 [25,26,27,28]. The fetal surgery results on the MMC are preliminary and probably due to several limiting factors including the timing of surgery, selection of the cases and technical difficulties [28, 29]. Our study suggests that other factors that have often been undervalued, such as vertical spinal cord stretching or even chemical aggression, may explain the upstream astrocytosis that goes well beyond the MMC limits and can be a further explanation for the suboptimal results of the in utero surgical repair.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] If results are not diagnostic, magnetic resonance imaging (MRI) is often used. 6 Although obviously an emotional diagnosis, it affords the family an opportunity to prepare themselves for the challenges ahead. Although controversial, in-utero closure of the open neural tube defect may offer some advantages to the child, but the risks of preterm labor (13% delivered at less than 30 weeks gestation) and maternal health remain significant concerns.…”
Section: Prenatalmentioning
confidence: 99%
“…If even the best operation is performed in the wrong patient, the results can be disastrous. 6,26,27 It has been shown that the most important factor in successful outcomes is proper family selection. [7][8][9]28 Bladder neck procedures range from endoscopic injections of the bladder neck to outpatient suburethral slings, to bladder neck reconstruction, to ligation or closure of the bladder neck.…”
Section: Elementary Schoolmentioning
confidence: 99%